Scatter view on European tax structures. Summary: Hajus vaade Euroopa Liidu riikide maksustruktuuridele - Trasberg, Viktor (Estonian Discussions on Economic Policy, 2013)
The paper analyses European Union countries tax structure changes during the last decade. Particular interest is related with correlations between tax structure and economic growth. There is argued, that the tax structure has an important impact on growth. The EU Commission proposes to shift tax burden from labor taxation to consumption to stimulate growth. However, is the tax structure and economic growth really related? The paper brings out structural changes in EU countries tax structures and impact of taxation to growth